Incidence and Outcomes of Severe Renal Impairment Following Ruptured Abdominal Aortic Aneurysm Repair. Issue 4 (October 2015) - Ambler, G.K.; Coughlin, P.A.; Hayes, P.D.; Varty, K.; Gohel, M.S.; Boyle, J.R.
Abstract : Introduction: Acute kidney injury (AKI) following ruptured abdominal aortic aneurysm (rAAA) repair is common and multifactorial. A standard definition of AKI after endovascular repair (EVAR), the Aneurysm Renal Injury Score (ARISe), has been proposed to facilitate standardised reporting and thus improve understanding of this issue. Methods: Data were collected retrospectively on AKI in a prospectively maintained database of all patients treated for rAAA in a single tertiary referral centre since the availability of routine out of hours emergency EVAR. The ARISe score was used to describe the degree of AKI and factors which correlated with poor renal outcomes were assessed. Results: Two-hundred and five patients were treated between January 2006 and April 2014. Of these, 125 were treated with open repair (OSR) and 80 were treated with EVAR. Severe AKI (defined as ARISe score ≥3) occurred in 36% of patients. After correction for confounders, patients treated with OSR were significantly more likely to develop severe AKI (43% vs. 26%, p = .02). There was no significant difference in preoperative serum creatinine between groups, but increased preoperative serum creatinine was strongly associated with severe AKI postoperatively ( p < .001). Age, sex, endograft type, and preoperative CT scanning were not associated with differences in renal outcomes. Clamp position above renal arteries was predictive of severe AKI in patients treated with OSR ( p < .01). Patients suffering severe AKI had significantly higher mortality at 30 days and 12 months (28% vs. 5% and 44% vs. 13%, p < .001 for both comparisons). Conclusion: Severe AKI is common following successful repair of rAAA. In this large case series of high-risk patients, OSR was associated with significantly higher rates of severe AKI compared with EVAR, despite the increased dose of contrast involved in EVAR and the older age of these patients. In turn, severe AKI was associated with higher mortality rates.